2016
DOI: 10.1186/s12909-016-0742-x
|View full text |Cite
|
Sign up to set email alerts
|

Training demands on clerk burnout: determining whether achievement goal motivation orientations matter

Abstract: BackgroundIn the education field, learning experiences are considered learners’ properties and are viewed as a key determinant in explaining learners’ learning processes, especially for training novices such as clerks with varying levels of commitment to the medical profession. This study explored whether clerks’ achievement goal motivation orientations might buffer the negative well-being to a certain extent, considering their training demands during clinical training.MethodsNinety-four clerks at a tertiary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The study participants were medical students from 2 cohorts who were studying in the 7-year doctor of medicine (MD) program of a university medical school in Taiwan and who had commenced their 2-year clinical workplace training clerkship in September 2013 and September 2014. All the training courses (in various specialties, which are listed in S1 Appendix ) [ 31 ] of the 2-year clerkship were organized by the department of education of the university-affiliated medical center. Of a total of 258 medical students from the 2 cohorts, 154 students signed informed consent forms (participation rate: 60%).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study participants were medical students from 2 cohorts who were studying in the 7-year doctor of medicine (MD) program of a university medical school in Taiwan and who had commenced their 2-year clinical workplace training clerkship in September 2013 and September 2014. All the training courses (in various specialties, which are listed in S1 Appendix ) [ 31 ] of the 2-year clerkship were organized by the department of education of the university-affiliated medical center. Of a total of 258 medical students from the 2 cohorts, 154 students signed informed consent forms (participation rate: 60%).…”
Section: Methodsmentioning
confidence: 99%
“…ProQOL originally covered 2 major constructs, namely compassion satisfaction and compassion fatigue (which is further divided into 2 components, namely burnout and secondary traumatic stress) [ 42 ]. It has been increasingly employed in studies on physicians [ 43 45 ] and medical students [ 31 , 46 ]. Most phenomena linked to secondary traumatic stress were unsuitable for the learning content and contexts of clinical clerkships.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior limited work in health professions education suggests associations between achievement goals (measured with various instruments) and academic performance, self-efficacy, burnout and frustration. [29][30][31][62][63][64][65][66] However, validity evidence for achievement goals assessments in the health professions has been sparsely reported.…”
Section: Integration With Prior Workmentioning
confidence: 99%
“…Whether before or after graduation, undergoing clinical training is more challenging than studying at school and can trigger many physical and mental health conditions (particularly mental disorders and emotional exhaustion) in medical students [13]. Studies have also revealed that medical students can encounter stressful clinical events [14] and psychological and physical demands [15, 16] during their clinical training years. A review study covering the peer-reviewed, English-language articles in MEDLINE between 1990 and 2015 revealed a prevalence of burnout among trainees, including medical students, residents, and interns, to a much higher level than found among the general population [17].…”
Section: Introductionmentioning
confidence: 99%